Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1002/sia.5205
|View full text |Cite
|
Sign up to set email alerts
|

In‐situ characterization of aqueous‐based hafnium oxide hydroxide sulfate thin films

Abstract: The dehydration of hafnium oxide hydroxide sulfate thin films was studied using temperature programmed desorption (TPD) and X-ray photoelectron spectroscopy. Films were found to desorb water up to 750 K with a maximum desorption rate at~480 K. Carbon dioxide desorption was also observed in TPD measurements, which was related to contamination of precursor solutions and/or films by CO 2 from the atmosphere. The O 1s spectra obtained for in-situ annealed samples were fit with three components corresponding to Hf-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…We found that the O 1s peak could be fit using two components. The higher binding energy ( E b ) peak A (532.0 eV) is attributed to sulfate and hydroxyl groups. , The lower E b peak B (530.2 eV) corresponds to a Hf–O–Hf oxide network, where this E b is similar to what has been observed for hafnium oxides. , For an initial XPS spectrum with limited X-ray exposure, peak B was considerably smaller than what was observed in Figure a. To investigate this phenomenon, O 1s spectra were collected repeatedly from the same sample area of a HafSOx film, and the changes in the spectra are shown in Figure b.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…We found that the O 1s peak could be fit using two components. The higher binding energy ( E b ) peak A (532.0 eV) is attributed to sulfate and hydroxyl groups. , The lower E b peak B (530.2 eV) corresponds to a Hf–O–Hf oxide network, where this E b is similar to what has been observed for hafnium oxides. , For an initial XPS spectrum with limited X-ray exposure, peak B was considerably smaller than what was observed in Figure a. To investigate this phenomenon, O 1s spectra were collected repeatedly from the same sample area of a HafSOx film, and the changes in the spectra are shown in Figure b.…”
Section: Resultsmentioning
confidence: 79%
“…Thus, HafSOx films in the exposure-ready condition may be visualized as a matrix of Hf cations, where peroxide is uniformly distributed on a subnanometer scale at a ratio of 1 peroxide per 2 hafnium ions, with sulfate and hydroxide competing for the remaining coordination sites and linking together the small clusters. While Hf−sulfate bonds in the material are thermally stable well above 70 °C, 43 Hf−hydroxide and Hf−peroxide are more susceptible to thermal decomposition. In particular, decomposition of Hf−peroxide during the PAB would eliminate the chemical contrast of the HafSOx thin film, and thus the thermal behavior of bound peroxide is critical to the function of the photoresist.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…While the in situ formation of H 2 O molecules on the HfO 2 surfaces from hydration of surface adsorbed species was confirmed, there was no tendency toward permanent disposition and distortion of the lattice component (O 2– ) on the surfaces. This leads us to the conclusion that the surfaces of the PEALD-grown HfO 2 films exhibit high stability toward H 2 and in situ-formed H 2 O as well as only minor defects that could facilitate degradation. , After a subsequent 30 min exposure to 5 mbar of O 2 gas at 25 °C, the chemisorbed oxygen ion and OH – -to-lattice-O 2– ratios remained unaffected in O 1s core-level spectra recorded (Figure S9). Besides, there were no notable changes in the O 1s and Hf 4f core-level regions or FWHM values, which might indicate surface reconstructions in the course of the O 2 exposure.…”
Section: Results and Discussionmentioning
confidence: 92%
“…This leads us to the conclusion that the surfaces of the PEALD-grown HfO 2 films exhibit high stability toward H 2 and in situ-formed H 2 O as well as only minor defects that could facilitate degradation. 61,63 After a subsequent 30 min exposure to 5 mbar of O 2 gas at 25 °C, the chemisorbed oxygen ion and OH − -to-lattice-O 2− ratios remained unaffected in O 1s core-level spectra recorded (Figure S9). Besides, there were no notable changes in the O 1s and Hf 4f core-level regions or FWHM values, In this case, residual gas analysis did not confirm the presence of water.…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 97%
“…For HafSO x films made without and with peroxide, water desorption (H 2 O, m/z 18, blue) occurs immediately as the temperature ramps above 320 K, peaking at 365 K and then decreasing to baseline through the range 450−800 K. In the peroxide film, H 2 O desorption has a slight local maximum at 440 K. The broad water desorption peak in this temperature range agrees with D 2 O TPD profiles from a prior study on HafSO x , which were assigned to both molecular and dissociative adsorption of water at low temperatures. 33 In the prior TGA of HafSO x powders, a mass loss below 473 K was attributed to the loss of constitutional H 2 O, whereas the mass loss between 473 and 973 K was attributed to the desorption of water via dehydroxylation. 5 In Figure 4b, the O 2 TPD spectrum of the HafSO x films containing peroxide has a broad intense peak with a maximum at 440 K. This desorption feature is absent for the HafSO x films without peroxide (Figure 4a).…”
Section: ■ Results and Discussionmentioning
confidence: 99%